Impact of endogenous canola phenolics on the oxidative stability of oil‐in‐water emulsions. Issue 5 (11th March 2013) - Sørensen, Ann‐Dorit Moltke; Friel, James; Winkler‐Moser, Jill K.; Jacobsen, Charlotte; Huidrom, Dayanidhi; Reddy, Narsi; Thiyam‐Holländer, Usha
Abstract The aim of this study was to evaluate the antioxidative effect of phenolics naturally present in canola seeds and meal. Individual phenolics were extracted from ground, defatted canola seeds, and meal. Fractionated extracts rich in sinapic acid, sinapine, or canolol as well as a non‐fractionated extract were used. These extracts (100 and 350 µM) were evaluated as antioxidants in stripped canola oil‐in‐water (o/w) emulsion. For comparison, the antioxidative effect of phenolic standards for sinapic acid and sinapine (as sinapine thiocyanate) and butylated hydroxytoluene (BTH) as a positive control were also evaluated. The concentration of lipid hydroperoxides and selected volatiles measured at different time points was used to evaluate the antioxidative effect. Moreover, the properties of extracts and corresponding phenolic standards were evaluated in three different in vitro antioxidant assays. All extracts and standard antioxidants had radical scavenging activity and reducing power. The antioxidant standards and extracts inhibited lipid oxidation in the emulsions compared to no antioxidant added. At 100 µM the effectiveness of the extracts was as follows: sinapine>whole extract>sinapic acid>canolol>Con2 (no antioxidant). At 350 µM the ranking was as follows: canolol ≥ sinapine ≥ whole extract ≥ sinapic acid > Con2. Sinapine and sinapic acid extracts were more efficient antioxidants than the corresponding pure standards. However, the most efficient antioxidant in this study was BHT. The differences in effectiveness may be ascribed to mainly the different chain attached to the phenolic ring, which results in different polarity and thus different location in the emulsions. Practical applications: The result showed stronger antioxidant activity of canola extracts than phenolic standards. Therefore, these canola extracts can be used for protecting canola oil emulsion or other emulsions against lipid oxidation. However, the results indicate that the antioxidant activity of the extracts rich in sinapine and canolol had a concentration‐sensitive effect. In order to get the best antioxidative effect, optimization of the concentration to be used for each specific application is necessary.